Trans* Politics and the Feminist Project: Revisiting the Politics of Recognition to Resolve Impasses - Saeidzadeh, Zara (2020)
The debates on, in, and between feminist and trans* movements have been politically intense at best and aggressively hostile at worst. The key contestations have revolved around three issues: First, the question of who constitutes a woman; second, what constitute feminist interests; and third, how trans* politics intersects with feminist politics. Despite decades of debates and scholarship, these impasses remain unbroken. In this article, our aim is to work out a way through these impasses. We argue that all three types of contestations are deeply invested in notions of identity, and therefore dealt with in an identitarian way. This has not been constructive in resolving the antagonistic relationship between the trans* movement and feminism. We aim to disentangle the antagonism within anti-trans* feminist politics on the one hand, and trans* politics’ responses to that antagonism on the other. In so doing, we argue for a politics of status-based recognition (drawing on Fraser, 2000a, 2000b) instead of identity-based recognition, highlighting individuals’ specific needs in society rather than women’s common interests (drawing on Jónasdóttir, 1991), and conceptualising the intersections of the trans* movement and feminism as mutually shaping rather than as trans* as additive to the feminist project (drawing on Walby, 2007, and Walby, Armstrong, and Strid, 2012). We do this by analysing the main contemporary scholarly debates on the relationship between the trans* movement and feminism within feminist and trans* politics. Unafraid of a polemic approach, our selection of material is strategic and illuminates the specific arguments put forward in the article.